Developing Halal Investment in the Islamic Capital Market in the Digital Era: A Literature Review Analysis - Ahmad Amirul Aziz; Taufiqur Rahman (Al-Iffah: Journal of Islamic Sciences Research, 2026)
This study discusses the development of halal investment in the Islamic capital market in the digital era through a systematic literature review (SLR) approach. This study aims to identify trends, opportunities, and challenges faced in the development of halal investment, as well as provide strategic recommendations to improve Islamic financial literacy. The methods used include analysis of relevant literature from 2020 to 2025, with a focus on digital innovation and financial inclusion. The results of the study indicate that although there is positive growth in interest in Islamic investment instruments, challenges such as low financial literacy and regulatory disharmony still hamper development. This study recommends collaboration between capital market authorities, fintech platforms, and educational institutions to improve public understanding of Islamic investment, as well as the integration of sustainability principles in investment products. Keywords: halal investment, Islamic capital market, financial literacy, digital innovation, and financial inclusion.